Mission - Valchev, Valentin (Bulgaria)
The health status of Roma people is lower then of other ethnic minorities in Bulgaria. The film follows three Health Mediators, social workers who help the Roma community in Varshetz, North Western Bulgaria.
Donation from OSI-Budapest Arts and Culture Program.
Duration: 00:30:00
Keywords: Documentary films